2019
DOI: 10.1596/1813-9450-9015
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Resilience in Sri Lanka: Natural Disaster Poverty and Wellbeing Impact Assessment

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Yang et al (2016) found that meteorological disasters significantly reduced farmers' incomes in specific areas and negatively affected farmers' agricultural and non-agricultural incomes. Walsh and Hallegatte (2019) incorporated socio-economic resilience into the risk assessment framework and found that floods would immediately lead Sri Lankans into poverty, especially for low-income groups. However, some scholars argued that disasters have a boosting effect on income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yang et al (2016) found that meteorological disasters significantly reduced farmers' incomes in specific areas and negatively affected farmers' agricultural and non-agricultural incomes. Walsh and Hallegatte (2019) incorporated socio-economic resilience into the risk assessment framework and found that floods would immediately lead Sri Lankans into poverty, especially for low-income groups. However, some scholars argued that disasters have a boosting effect on income.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, researchers strengthen social resilience in mountain communities by researching the adverse effects of disasters and climate change in India's underdeveloped regions (Barua et al, 2014). More efficient solutions can be developed by considering Sri Lanka's socioeconomic resilience, poverty rates, and social welfare (Walsh & Hallegatte, 2019). China has also implemented several policies to fight poverty.…”
Section: Introductionmentioning
confidence: 99%